An Analysis of the Implementation and Effectiveness of the Aqidah Learning Curriculum at Pondok Modern Darussalam Gontor - Mukri, Rusdiono; Hafidhuddin, Didin; Bahruddin, E.; Indra, Hasbi (Indo Consultan Energi, 2025)
This study aims to determine the implementation of the aqidah learning curriculum at the Modern Islamic Boarding School of Darussalam Gontor. This study uses a qualitative approach with a descriptive approach. Then, the primary data source for this study was obtained through direct observation at the research location and interviews with the leaders of the Modern Islamic Boarding School of Gontor and the aqidah learning curriculum development team. At the same time, secondary data were obtained from documents, books, magazines, and journals. The study results indicate that implementing the aqidah learning curriculum at the Modern Islamic Boarding School of Darussalam Gontor is carried out in class, outside class, and in the dormitory. The talqin method, lectures, discussions, questions and answers, recitations, prayers, dictations (imla), and memorization methods are used in class. The material for grades 1–3 discusses the pillars of Islam, while grades 4–6 discuss the pillars of faith. The material for grade 1 is delivered in Indonesian, and for subsequent classes, it is delivered using Arabic. While outside the classroom, aqidah learning is delivered using the talaqqi method, amaliyah practice, halaqah, mudzakarah, and demonstration methods. The teaching of aqidah is also strengthened through good deeds. To improve the quality of aqidah learning, the author recommends using a dialogue method between philosophy and Islamic aqidah. With this method, students are taught to understand the challenges of modern thought and answer them with Islamic arguments. In addition, it is also necessary to learn aqidah in a contemporary context by training students to apply the concept of aqidah in everyday life, especially in facing modern phenomena such as liberalism, secularism, materialism, and pluralism, as well as the challenges of digital technology developments that influence the process and implementation of learning.